Vestibular Dysfunction and Gross Motor Milestone Acquisition in Children With Hearing Loss: A Systematic Review. (12th January 2021) - Singh, Anisha; Raynor, Eileen M.; Lee, Janet W.; Smith, Sherri L.; Heet, Hannah; Garrison, Doug; Wrigley, Jordan; Kaylie, David M.; Riska, Kristal M.
Abstract : Objective: To describe the impact of vestibular dysfunction on gross motor development in children with hearing loss. Data Sources: MEDLINE (PubMed), Embase (Elsevier), Web of Science (Clarivate), and the Cumulative Index of Nursing and Allied Health Literature (EBSCO). Review Methods: A systematic review was reported in concordance with the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta‐analyses). Articles on children with hearing loss who underwent at least 1 instrumented measure of vestibular function and had gross motor milestones assessed were included. The Downs and Black checklist was used to assess risk of bias and methodological quality. Results: Eleven articles were included in the systematic review. Three articles stratified quantitative results of gross motor milestone acquisition by severity of vestibular impairment. Over half of studies were case series published within the last 5 years. This systematic review showed that children with hearing loss and severe, bilateral vestibular dysfunction demonstrate delayed gross motor milestones. However, it was difficult to draw conclusions on whether milder forms of vestibular dysfunction significantly affect gross motor milestone acquisition in children with hearing loss. The reason is that most studies were of low to moderate quality, used different assessment methods, and contained results that were descriptive in nature. Conclusions: This emerging area would benefit from future research, such as higher‐quality studies to assess vestibular function and gross motor milestones. This would allow for better characterization of the impacts of vestibular impairment, especially milder forms, in children with hearing loss.